Pengaruh Literasi Keuangan, Inklusi Keuangan, Dan Sumber Modal Terhadap Pengelolaan Keuangan UMKM Di Kecamatan Jatibarang Kabupaten Brebes - Yasminudin Yasminudin; Indah Dewi Mulyani; Nur Afridah (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research was conducted on MSMEs throughout Jatibarang District, Brebes Regency. This research aims to determine the influence of financial literacy, financial inclusion and capital sources on MSME financial management. This research is a type of quantitative research. The data collection method used in this research was by distributing questionnaires to MSME actors selected as samples. The sample for this research was 100 MSME actors, using a sample, namely non-probability sampling with a purposive sampling technique. The data analysis for this research is multiple linear regression analysis assisted by tools in the form of SPSS version 25. The data obtained is primary data, while secondary data is obtained from other media such as books and journals related to the focus of this research. The results of this research show that financial literacy has a significant effect on the financial management of MSMEs with a t table value of (4.801 > 2.626) and a significant value of (0.000 < 0.05), financial inclusion has no effect but there is a relationship between financial inclusion and financial management with The calculated t value is smaller than the t table value, namely (2.115 < 2.626) while it is significant, namely (0.037 < 0.05, and the source of capital does not have a significant effect on financial management with the calculated t value being greater than the t table value, namely (1.679 < 2,626). Meanwhile, the significant value is (0.096 > 0.05). Then the results of the simultaneous test show that the variables financial literacy, financial inclusion, and capital sources have an effect on MSME financial management with the significance value obtained being less than 0.05, or F calculated is greater than F table = 42.254 greater than 3.089.